2019
DOI: 10.21608/adjalexu.2019.57577
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Topically Applied Hyaluronic Acid Gel Versus Topical Corticosteroid in the Treatment of Erosive Oral Lichen Planus

Abstract: INTRODUCTION: Oral lichen planus is a common chronic inflammatory muco-cutaneous disease. Although the cause of oral lichen planus is not well known, T-lymphocyte infiltrate suggests a cell mediated immunological damage to basal cell layer of the epithelium. Its suggested treatment is topical corticosteroid. A promising new treatment for oral lichen planus [OLP] is the topical application of hyaluronic acid [HA], which has shown beneficial effect on wound healing. OBJECTIVES: to evaluate the effect of hyaluron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Five studies reported a high risk of bias [ 6 14 15 18 19 ] due to one or more risks owing to performance, detection, attrition, and reporting bias. Two other studies reported an unclear risk of bias in selection, performance, and detection [ 13 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies reported a high risk of bias [ 6 14 15 18 19 ] due to one or more risks owing to performance, detection, attrition, and reporting bias. Two other studies reported an unclear risk of bias in selection, performance, and detection [ 13 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 199 participants from 6 studies were included in the analysis of OLP lesion symptoms [ 6 13 15 18 19 20 ]. The pooled overall mean difference was 0.65 [95% CI: -1.80 to 3.09] which was not statistically significant (Z = 0.52, P = 0.60).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations